Letter to the Editor: a response. (23rd September 2008) - Feinendegen, Ludwig E.; Paretzke, Herwig G.; Neumann, Ronald D.
A response to Louis de Saint-Georges' comment on the paper: Feinendegen, L.E., Paretzke, H.G. and Neumann, R.D. (2007), 'Damage propagation in complex biological systems following exposure to low doses of ionising radiation', Atoms for Peace: An International Journal, Vol. 1, No.4, pp.336?354.